Parameterized Verification of Multithreaded Software Libraries - Ball, Thomas; Chaki, Sagar; Rajamani, Sriram (Microsoft, 2000)
The growing popularity of multi-threading has led to a great number of software libraries that support access by multiple threads. We present Local/Global Finite State Machines (LGFSMs) as a model for a certain class of multithreaded libraries. We have developed a tool called Beacon that does parameterized model checking of LGFSMs . We demonstrate the expressiveness of LGFSMs as models, and the effectiveness of Beacon as a model checking tool by (1) modeling a multithreaded memory manager Rockall developed at Microsoft Research as an LGFSM , and (2) using Beacon to check a critical safety property of Rockall.